Roles of Soybean Plasma Membrane Intrinsic Protein GmPIP2;9 in Drought Tolerance and Seed Development - Lu, Linghong; Dong, Changhe; Liu, Ruifang; Zhou, Bin; Wang, Chuang; Shou, Huixia (Frontiers in Plant Science, 2018)
Aquaporins play an essential role in water uptake and transport in vascular plants. The soybean genome contains a total of 22 PIP genes. To identify candidate PIPs important for soybean yield and stress tolerance, we studied the transcript levels of all 22 soybean PIPs. We found that a GmPIP2 subfamily member, GmPIP2;9, was predominately expressed in roots and developing seeds. Here, we show that GmPIP2;9 localized to the plasma membrane and had high water channel activity when expressed in Xenopus oocytes. Using transgenic soybean plants expressing a native GmPIP2;9 promoter driving a GUS-reporter gene, it was found that high GUS expression in the roots, in particular, in the endoderm, pericycle, and vascular tissues of the roots of transgenic plants. In addition, GmPIP2;9 was also highly expressed in developping pods. GmPIP2;9 expression significantly increased in short term of polyethylene glycol (PEG)-mediated drought stress treatment. GmPIP2;9 overexpression increased tolerance to drought stress in both solution cultures and soil plots. Drought stress in combination with GmPIP2;9 overexpression increased net CO2 assimilation of photosynthesis, stomata conductance, and transpiration rate, suggesting that GmPIP2;9-overexpressing transgenic plants were less stressed than wild-type plants. Furthermore, field experiments showed that GmPIP2;9-overexpressing plants had significantly more pod numbers and larger seed sizes than wild-type plants. In summary, the study demonstrated that GmPIP2;9 has water transport activity. Its relative high expression levels in roots and developing pods is in agreement with the phenotypes of GmPIP2;9-overexpressing plants in drought stress tolerance and seed development.